Tomographic analysis of nasomaxillary and zygomaticomaxillary buttress bone thickness for the fixation of miniplates. Issue 8 (August 2021) - Medeiros, Y.L.; Loures, A.O.; Silva, B.N.; Reher, P.; Devito, K.L.; Carvalho, M.F.
Abstract: The purpose of this study was to evaluate the bone thickness of the nasomaxillary and zygomaticomaxillary buttresses to identify the most favourable region for the installation of miniplates. Bilateral tomographic images of 103 individuals were evaluated, for a total of 206 nasomaxillary and zygomaticomaxillary buttresses. Measurements of bone thickness were performed in the parasagittal reconstructions along three vertical lines on the nasomaxillary buttress (21 measurement points) and four vertical lines on the zygomaticomaxillary buttress (28 measurement points). The vertical line measurements for each buttress were compared using the Kruskal–Wallis test. Spearman's correlation coefficient was used to determine the correlation between the thicknesses obtained and patient sex and side (right/left). The level of significance adopted was 5%. The nasomaxillary and zygomaticomaxillary buttresses presented statistical differences in thickness at their respective points ( P = 0.001). The analysis of the nasomaxillary buttress showed that the thicker bone for the installation of miniplates follows the long axis of the upper canine at a distance of 3 mm from the root apex. For the zygomaticomaxillary buttress, thicker bone to install miniplates was found distal to the distobuccal root of the first molar, at a distance of 3.5 mm from the limit of the infraorbital foramen.